Internet-based cognitive-behavioral therapy is effective in reducing depressive symptomatology in type 1 diabetes: results of a randomized controlled trial - Carreira, Mónica; Ruiz de Adana, Ma Soledad; Pinzón, José Luis; Anarte-Ortiz, María Teresa (Frontiers in Clinical Diabetes and Healthcare, 2023)
Objective Depression in people with diabetes is associated with poorer health outcomes. Although web programs integrating cognitive-behavioral therapy with diabetes education have shown good results, no similar approach has been implemented in Spain. This aim of this study was to administer an Internet-based cognitive-behavioral therapy program (CBT) for the treatment of mild-moderate depressive symptomatology in individuals with type 1 diabetes (WEB_TDDI1 study) and evaluate the efficacy of this program. Research design and methods A pre-post randomized controlled study was conducted. The sample comprised 65 people with type 1 diabetes and mild-moderate depressive symptoms: 35 treatment group (TG) and 30 control group (CG). The following effects of the nine-session program were analyzed: depression (Beck Depression Inventory Fast Screen, BDI-FS), metabolic variables (glycosilated hemoglobin, HbA1c), and other psychological variables including anxiety (State Trait Anxiety Inventory, STAI), fear of hypoglycemia (Fear of Hypoglycemia Questionnaire, FH-15), distress (Diabetes Distress Questionnaire (DDS), quality of life (Diabetes Quality of Life Questionnaire, DQOL),and treatment adherence (Diabetes Self-Care Inventory-Revised questionnaire, SCI-R). Results At the end of the treatment program, only 28 people were evaluated (TG=8; CG=20). However, a significant reduction was found in both groups in BDI-FS and STAI-T scores, which was significantly greater in the TG. Significant improvements were also found in the TG in DQOL, FH-15, DDS and SCI-R scores. The percentage change in these variables was also statistically significant in the TG versus the CG. However, no significant results were found in HbA1c. Conclusions The Internet-based cognitive-behavioral therapy program for the treatment of mild-moderate depressive symptomatology in people with type 1 diabetes (WEB_TDDI1 study) is effective in reducing depressive symptomatology in the sample that completed the study. Positive results are also produced in other variables associated with depression in this population such as diabetes-related distress, trait anxiety, fear of hypoglycemia, quality of life, and adherence to diabetes treatment. Although new studies would be necessary to support the results of this platform, the results obtained are positive and support the use of this platform as an appropriate treatment for this population. Clinical trial registration ClinicalTrials.gov; identifier NCT03473704.